Happy Enough to Relax? How Positive and Negative Emotions Activate Different Muscular Regions in the Back - an Explorative Study - Scheer, Clara; Kubowitsch, Simone; Dendorfer, Sebastian; Jansen, Petra (Frontiers in Psychology, 2021)
Muscular reactions provide humans a crucial tool for social communication. The aim of the following study was firstly to examine whether muscle activity patterns are elevated through opposed emotions, positive and negative, and secondly whether these emotions affect different back regions. Electromyographic (EMG) activity of six back muscles was recorded in 31 healthy subjects during exposure to positive and negative affective pictures. A resting period was used as control condition. Increased muscle activity patterns in the back were found during exposure to the negative emotion, which was mainly measured in the lumbar and the thorax region. The positive emotion caused no elevated activity. The present study shows that negative emotions lead to increased differential muscle activity in the back and thus highlights the importance of bodily expression for social communication.